Method for producing inorganic material

Through the ball mill grinding and mesh separation device separation technology, the problem of easy aggregation of sulfide-based all-solid lithium-ion battery materials in the manufacturing process is solved, and fine particles are obtained, which improves the energy density and production efficiency of the battery.

JP2025039629AInactive Publication Date: 2025-03-21FURUKAWA COMPANY
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024232834
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-10-15
Filing Date
2024-12-27
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The solid electrolytic materials in existing sulfide-based all-solid lithium-ion batteries are soft and easy to aggregate because they contain sulfur, make it difficult to control the particle size and avoid aggregation during the manufacturing process.

Method used

The first sulfide-based material is ground by using a ball mill, and a second sulfide-based material with fine particles is generated by rotating and moving the ball mill container, and the material attached to the grinding ball is separated out through a mesh separation device.

Benefits of technology

The aggregation of materials is effectively inhibited, and a sulfide-based material with an average particle size is obtained, which increases the energy density of the battery and simplifies the production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039629000001_ABST
    Figure 2025039629000001_ABST
Patent Text Reader

Abstract

To provide a method for producing an inorganic material, which can suppress generation of an aggregate and provide an inorganic material small in an average particle diameter.SOLUTION: This method for producing an inorganic material comprises: a step (A) of preparing a first inorganic material serving as a raw material; a step (B) of atomizing the first inorganic material to provide a second inorganic material by crushing the first inorganic material using a ball mill formed of a cylindrical vessel and a pulverizing ball; and a step (C) of separating the second inorganic material from the pulverizing ball having the second pulverizing ball stuck thereto. The step (B) includes a step (B1) of entering the first inorganic material and the pulverizing ball into the cylindrical vessel and then rotating the cylindrical vessel about a cylindrical axis, and a step (B2) of moving the cylindrical vessel so as to move the first inorganic material in the cylindrical axis direction.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing inorganic materials. [Background technology]

[0002] Lithium-ion batteries are generally used as power sources for small portable devices such as mobile phones and laptops, etc. Recently, lithium-ion batteries have also begun to be used as power sources for electric vehicles, power storage, and other devices in addition to small portable devices.

[0003] Currently available lithium-ion batteries use electrolytes that contain flammable organic solvents. On the other hand, lithium-ion batteries that use a solid electrolyte to make the battery all-solid-state (hereinafter also referred to as all-solid-state lithium-ion batteries) do not use flammable organic solvents in the battery, which allows for simplified safety devices and is thought to be superior in terms of manufacturing costs and productivity.

[0004] As a solid electrolyte material used for such a solid electrolyte, for example, a sulfide-based solid electrolyte material is known.

[0005] In Patent Document 1 (JP 2016-27545 A), a peak is observed at 2θ=29.86°±1.00° in X-ray diffraction measurement using CuKα radiation, and Li 2y+3 A sulfide-based solid electrolyte material is described that is characterized by having a composition of PS4 (0.1≦y≦0.175). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2016-27545 A Summary of the Invention [Problem to be solved by the invention]

[0007] The energy density of an all-solid-state lithium-ion battery can be increased, for example, by reducing the proportion of solid electrolyte material in the electrode active material layer or by reducing the thickness of the solid electrolyte layer provided between the positive electrode and the negative electrode. Here, in order to reduce the proportion of the solid electrolyte material in the electrode active material layer and to reduce the thickness of the solid electrolyte layer, it is preferable that the solid electrolyte material has a small average particle size. According to the investigations of the present inventors, it has become clear that the sulfide-based inorganic solid electrolyte material described in Patent Document 1 is soft because it contains sulfur, and when it is crushed strongly, it may aggregate and adhere to the inner wall of the cylindrical container.

[0008] The present invention has been made in view of the above circumstances, and provides a method for producing an inorganic material that can suppress the formation of aggregates and produce an inorganic material having a small average particle size. [Means for solving the problem]

[0009] One aspect of the present invention is A step (A) of preparing a first inorganic material as a raw material; (B) a step of pulverizing the first inorganic material using a ball mill having a cylindrical container and pulverizing balls to obtain a second inorganic material by microparticulating the first inorganic material; (C) a step of separating the second inorganic material from the grinding balls to which the second inorganic material is attached; Including, The step (B) includes a step (B1) of rotating the cylindrical container about a cylindrical axis after placing the first inorganic material and the grinding balls in the cylindrical container, and a step (B2) of moving the cylindrical container so that the first inorganic material moves in the cylindrical axis direction. The present invention relates to a method for producing an inorganic material comprising the steps of: Effect of the Invention

[0010] According to the above aspect of the present invention, it is possible to provide a method for producing an inorganic material that can suppress the formation of aggregates and obtain an inorganic material having a small average particle size. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a schematic diagram for explaining the motion of the ball mill in Examples 1-2 and a Comparative Example, where (a) is Examples 1-2 and (b) is the Comparative Example. [Diagram 2] 3 is a schematic top view of a separation device used in step (C) of the method for producing an inorganic material according to the first embodiment. FIG. [Diagram 3] FIG. 3 is a schematic cross-sectional view along the line AA′ of FIG. [Figure 4] 2 is an enlarged schematic view of a portion of the mesh member according to the first embodiment. FIG. [Diagram 5] FIG. 11 is a schematic top view of a separation device according to a second embodiment. [Figure 6] FIG. 11 is a schematic side view of a separation device according to a second embodiment. [Figure 7] FIG. 6 is a schematic cross-sectional view of FIG. 5 along the line B-B'. [Figure 8] FIG. 11 is an enlarged schematic view of a portion of a mesh member according to a second embodiment. [Figure 9] FIG. 13 is a schematic diagram of a separation device according to a modified example. [Figure 10] FIG. 2 shows an SEM image of the second inorganic material separated from the grinding balls in Example 1. [Figure 11] FIG. 13 shows an SEM image of the second inorganic material separated from the grinding balls in Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In all drawings, similar components are given the same reference numerals and the description will be omitted as appropriate. The numerical range "A to B" indicates A or more and B or less unless otherwise specified.

[0013] (Embodiment 1) The method for producing an inorganic material according to embodiment 1 includes a step (A) of preparing a first inorganic material as a raw material, a step (B) of grinding the first inorganic material using a ball mill consisting of a cylindrical container and grinding balls to microparticulate the first inorganic material to obtain a second inorganic material, and a step (C) of separating the second inorganic material from the grinding balls to which the second inorganic material is attached, and the step (B) includes a step (B1) of rotating the cylindrical container about its cylindrical axis after placing the first inorganic material and the grinding balls in the cylindrical container, and a step (B2) of moving the cylindrical container so that the first inorganic material moves in the direction of the cylindrical axis.

[0014] According to the method for producing an inorganic material according to the present embodiment, it is possible to suppress the generation of aggregates and obtain an inorganic material having a small average particle size. In addition, it is possible to cause the second inorganic material to adhere to the grinding balls rather than to the inner wall of the cylindrical container, and it is possible to recover the second inorganic material adhered to the grinding balls.

[0015] Each step will be described in detail below.

[0016] (Process (A)) First, the first inorganic material is prepared as a raw material. The first inorganic material may be manufactured or may be a commercially available product. The first inorganic material is not particularly limited as long as it is a material that requires microparticulation, and examples thereof include inorganic solid electrolyte materials, positive electrode active materials, and negative electrode active materials.

[0017] The inorganic solid electrolyte material is not particularly limited, but examples thereof include sulfide-based inorganic solid electrolyte materials, oxide-based inorganic solid electrolyte materials, other lithium-based inorganic solid electrolyte materials, etc. Among these, sulfide-based inorganic solid electrolyte materials are preferred. The inorganic solid electrolyte material is not particularly limited, but examples thereof include those used in solid electrolyte layers constituting all-solid-state lithium ion batteries.

[0018] Examples of sulfide-based inorganic solid electrolyte materials include, for example, Li2S-P2S5 materials, Li2S-SiS2 materials, Li2S-GeS2 materials, Li2S-Al2S3 materials, Li2S-SiS2-Li3PO4 materials, Li2S-P2S5-GeS2 materials, Li2S-Li2O-P2S5-SiS2 materials, Li2S-GeS2-P2S5-SiS2 materials, Li2S-SnS2-P2S5-SiS2 materials, Li2S-P2S5-Li3N materials, Li2S 2+X -P4S3 materials, Li2S-P2S5-P4S3 materials, and the like. Among these, Li2S-P2S5 materials and Li2S-P2S5-Li3N materials are preferred because they have excellent lithium ion conductivity and stability that do not cause decomposition or the like in a wide voltage range. Here, for example, the Li2S-P2S5 material means an inorganic material obtained by chemically reacting at least Li2S (lithium sulfide) and P2S5 with each other by mechanical treatment, and the Li2S-P2S5-Li3N material means an inorganic material obtained by chemically reacting at least Li2S (lithium sulfide), P2S5, and Li3N with each other by mechanical treatment. Here, in this embodiment, lithium sulfide includes polysulfide lithium.

[0019] Examples of the above oxide-based inorganic solid electrolyte materials include NASICON types such as LiTi2(PO4)3, LiZr2(PO4)3, LiGe2(PO4)3, and perovskite types such as (La 0.5+x Li 0.5-3x )TiO3, Li2O-P2O5 materials, Li2O-P2O5-Li3N materials, and the like. Examples of other lithium-based inorganic solid electrolyte materials include, for example, LiPON, LiNbO3, LiTaO3, Li3PO4, LiPO 4-x N x (x where 0 < x ≤ 1), LiN, LiI, LISICON, and the like. Furthermore, glass ceramics obtained by precipitating crystals of these inorganic solid electrolytes can also be used as inorganic solid electrolyte materials.

[0020] The sulfide-based inorganic solid electrolyte material according to this embodiment preferably contains, as constituent elements, Li, P and S. In addition, the sulfide-based inorganic solid electrolyte material according to this embodiment is preferably in a glass state as the first inorganic material, from the viewpoint of obtaining a smaller average particle diameter.

[0021] In addition, in the sulfide-based inorganic solid electrolyte material according to this embodiment, from the viewpoint of further improving lithium ion conductivity, electrochemical stability, stability in moisture and air, and ease of handling, the molar ratio (Li / P) of the Li content to the P content in the solid electrolyte material is preferably 1.0 to 10.0, more preferably 2.0 to 5.0, even more preferably 2.5 to 4.0, even more preferably 2.8 to 3.6, even more preferably 3.0 to 3.5, even more preferably 3.1 to 3.4, and particularly preferably 3.1 to 3.3. In addition, the molar ratio (S / P) of the S content to the P content is preferably 1.0 to 10.0, more preferably 2.0 to 6.0, even more preferably 3.0 to 5.0, even more preferably 3.5 to 4.5, even more preferably 3.8 to 4.2, even more preferably 3.9 to 4.1, and particularly preferably 4.0. Here, the contents of Li, P, and S in the solid electrolyte material of this embodiment can be determined by, for example, ICP emission spectroscopy or X-ray photoelectron spectroscopy.

[0022] The sulfide-based inorganic solid electrolyte material according to this embodiment can be used in any application requiring lithium ion conductivity. In particular, the sulfide-based inorganic solid electrolyte material according to this embodiment is preferably used in a lithium ion battery. More specifically, it is used in a positive electrode active material layer, a negative electrode active material layer, an electrolyte layer, etc. in a lithium ion battery. Furthermore, the sulfide-based inorganic solid electrolyte material according to this embodiment is preferably used in a positive electrode active material layer, a negative electrode active material layer, a solid electrolyte layer, etc. constituting an all-solid-state lithium ion battery, and is particularly preferably used in a solid electrolyte layer constituting an all-solid-state lithium ion battery. An example of an all-solid-state lithium ion battery using the sulfide-based inorganic solid electrolyte material according to this embodiment is one in which a positive electrode, a solid electrolyte layer, and a negative electrode are laminated in this order.

[0023] The positive electrode active material is not particularly limited, and examples thereof include positive electrode active materials that can be used in the positive electrode layer of a lithium ion battery. For example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), solid solution oxide (Li2MnO3-LiMO2 (M=Co, Ni, etc.)), lithium manganese nickel oxide (LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2), olivine-type lithium phosphate oxide (LiFePO4), and other composite oxides; sulfide-based positive electrode active materials, such as CuS, Li-Cu-S compounds, TiS2, FeS, MoS2, V2S5, Li-Mo-S compounds, Li-Ti-S compounds, Li-VS compounds, and Li-Fe-S compounds; and the like.

[0024] The negative electrode active material is not particularly limited, and examples thereof include negative electrode active materials that can be used in the negative electrode layer of a lithium ion battery. For example, metallic materials mainly composed of lithium alloys, tin alloys, silicon alloys, gallium alloys, indium alloys, aluminum alloys, etc.; lithium titanium composite oxides (e.g., Li4Ti5O 12 ); graphite-based materials, etc.

[0025] A method for producing a sulfide-based inorganic solid electrolyte material in a glassy state will be described below. A sulfide-based inorganic solid electrolyte material in a glassy state can be obtained, for example, by preparing a mixture containing lithium sulfide and phosphorus sulfide, and then mechanically treating the mixture to vitrify the raw materials lithium sulfide and phosphorus sulfide while causing a chemical reaction.

[0026] The mixture containing lithium sulfide and phosphorus sulfide can be obtained, for example, by mixing the respective raw materials in a predetermined molar ratio so that the target sulfide-based inorganic solid electrolyte material has a desired composition ratio. Here, the mixing ratio of each raw material in the mixture is adjusted so that the resulting sulfide-based inorganic solid electrolyte material has a desired composition ratio. The method for mixing the raw materials is not particularly limited as long as it can mix the raw materials uniformly. For example, the raw materials can be mixed using a ball mill, a bead mill, a vibration mill, an impact grinding device, a mixer (a pug mixer, a ribbon mixer, a tumbler mixer, a drum mixer, a V-type mixer, etc.), a kneader, a two-shaft kneader, an airflow grinder, etc. The mixing conditions when mixing the raw materials, such as the stirring speed, processing time, temperature, reaction pressure, and gravitational acceleration applied to the mixture, can be appropriately determined depending on the processing amount of the mixture.

[0027] The lithium sulfide used as the raw material is not particularly limited, and commercially available lithium sulfide may be used, or lithium sulfide obtained by reacting lithium hydroxide with hydrogen sulfide may be used. From the viewpoint of obtaining a high-purity sulfide-based inorganic solid electrolyte material and suppressing side reactions, it is preferable to use lithium sulfide with few impurities. In this embodiment, the lithium sulfide includes lithium polysulfide. Li2S is preferable as the lithium sulfide.

[0028] The phosphorus sulfide used as the raw material is not particularly limited, and commercially available phosphorus sulfides (e.g., P2S5, P4S3, P4S7, P4S5, etc.) can be used. From the viewpoint of obtaining a high-purity sulfide-based inorganic solid electrolyte material and from the viewpoint of suppressing side reactions, it is preferable to use phosphorus sulfide with few impurities. As the phosphorus sulfide, P2S5 is preferable.

[0029] Lithium nitride may also be used as a raw material. Here, since the nitrogen in lithium nitride is discharged into the system as N2, by using lithium nitride as a raw material, it becomes possible to increase only the Li composition in a sulfide-based inorganic solid electrolyte material that contains Li, P, and S as constituent elements. The lithium nitride according to the present embodiment is not particularly limited, and may be commercially available lithium nitride (e.g., Li3N, etc.), or may be obtained by reacting metallic lithium (e.g., Li foil) with nitrogen gas. From the viewpoint of obtaining a high-purity solid electrolyte material and suppressing side reactions, it is preferable to use lithium nitride with few impurities.

[0030] Next, the mixture containing lithium sulfide and phosphorus sulfide is mechanically treated to vitrify the raw materials lithium sulfide and phosphorus sulfide while causing a chemical reaction, thereby obtaining a sulfide-based inorganic solid electrolyte material in a glassy state. The mechanical treatment herein is a treatment in which two or more inorganic compounds are mechanically collided with each other to cause a chemical reaction and thereby vitrification, and examples thereof include mechanochemical treatment. Furthermore, from the viewpoint of easily realizing an environment in which moisture and oxygen are removed to a high degree in the vitrification step, the mechanical treatment is preferably carried out in a dry manner, and a dry mechanochemical treatment is more preferable. By using the mechanochemical treatment, the raw materials can be mixed while being pulverized into fine particles, so that the contact area of ​​the raw materials can be increased, which promotes the reaction of the raw materials, and thus makes it possible to more efficiently obtain a sulfide-based inorganic solid electrolyte material in a glassy state.

[0031] Here, mechanochemical treatment is a method of vitrification while applying mechanical energy such as shear force, impact force, or centrifugal force to the target composition. Apparatuses for vitrification by mechanochemical treatment include crushing and dispersing machines such as ball mills, bead mills, vibration mills, turbo mills, mechanofusion, disk mills, and roll mills; rotary impact crushing machines consisting of a mechanism combining rotation (shear stress) and impact (compressive stress) represented by rock drills, vibration drills, impact drivers, etc.; and high-pressure gliding rolls. Among these, ball mills and bead mills are preferred from the viewpoint of efficiently generating very high impact energy, and ball mills are particularly preferred. In addition, from the viewpoint of excellent continuous productivity, roll mills; rotary impact crushing machines consisting of a mechanism combining rotation (shear stress) and impact (compressive stress) represented by rock drills, vibration drills, impact drivers, etc.; and high-pressure gliding rolls, etc. are preferred.

[0032] In addition, the mechanochemical treatment is preferably carried out in an inert atmosphere, which can suppress reactions between the sulfide-based inorganic solid electrolyte material and water vapor, oxygen, and the like. The inert atmosphere means a vacuum atmosphere or an inert gas atmosphere. In the inert atmosphere, the dew point is preferably -30°C or less, more preferably -50°C or less, and particularly preferably -60°C or less, to avoid contact with moisture. The inert gas atmosphere means an atmosphere of an inert gas such as argon gas, helium gas, or nitrogen gas. These inert gases are preferably as high in purity as possible to prevent impurities from being mixed into the product. The method of introducing the inert gas into the mixed system is not particularly limited as long as the mixed system is filled with an inert gas atmosphere, and examples thereof include a method of purging the inert gas and a method of continuously introducing a constant amount of the inert gas.

[0033] The mixing conditions, such as the rotation speed, processing time, temperature, reaction pressure, and gravitational acceleration applied to the mixture, when mechanically processing the mixture containing lithium sulfide and phosphorus sulfide, can be appropriately determined depending on the type and processing amount of the mixture. In general, the faster the rotation speed, the faster the glass production rate, and the longer the processing time, the higher the conversion rate to glass. Typically, when X-ray diffraction analysis is performed using CuKα radiation as the radiation source, if the diffraction peaks derived from the raw materials disappear or decrease, it can be determined that the mixture has been vitrified and a sulfide-based inorganic solid electrolyte material in a glassy state has been obtained.

[0034] Here, in the process of vitrifying the mixture containing lithium sulfide and phosphorus sulfide, the lithium ion conductivity by the AC impedance method under the measurement conditions of 27.0 °C, applied voltage of 10 mV, and measurement frequency range of 0.1 Hz to 7 MHz is 0.5 × 10 -4 S cm -1 More than 1.0×10 -4 S cm -1 It is preferable to carry out the mechanical treatment until the above-mentioned temperature is reached, whereby a sulfide-based inorganic solid electrolyte material having even more excellent lithium ion conductivity can be obtained.

[0035] (Process (B)) Next, in a manner similar to the example shown in Figure 1(a) described below, the first inorganic material prepared in step (A) is pulverized using a ball mill consisting of a cylindrical container and grinding balls, thereby converting the first inorganic material into fine particles to obtain a second inorganic material. Step (B) includes a step (B1) of placing a first inorganic material and grinding balls in a cylindrical container, and then rotating the cylindrical container about its cylindrical axis, and a step (B2) of moving the cylindrical container so that the first inorganic material moves in the cylindrical axial direction. Here, step (B1) and step (B2) may be carried out simultaneously or separately. Moreover, step (B2) may be carried out continuously or intermittently while carrying out step (B1).

[0036] In step (B), it is preferable to pulverize the first inorganic material in a dry state. When pulverized in a dry state, the organic solvent or water used as a dispersion medium is not required, which can prevent the inorganic material from reacting with organic molecules or from deteriorating due to hydrolysis, and further, the step of separating the organic solvent or water is not required, which can simplify the manufacturing process. In this embodiment, the ball mill consisting of a cylindrical container and grinding balls is a ball mill that rotates around a cylindrical axis, and does not include planetary motion type ball mills.

[0037] Moreover, it is preferable to carry out the step (B) in an inert atmosphere, which can suppress reactions between the inorganic material and water vapor, oxygen, etc. The inert atmosphere means a vacuum atmosphere or an inert gas atmosphere. In the inert atmosphere, the dew point is preferably -30°C or less, more preferably -50°C or less, and particularly preferably -60°C or less, to avoid contact with moisture. The inert gas atmosphere means an atmosphere of an inert gas such as argon gas, helium gas, or nitrogen gas. These inert gases are preferably as high in purity as possible to prevent impurities from being mixed into the product. The method of introducing the inert gas into the mixed system is not particularly limited as long as the mixed system is filled with an inert gas atmosphere, and examples thereof include a method of purging the inert gas and a method of continuously introducing a constant amount of the inert gas.

[0038] The grinding conditions in step (B), such as the treatment time, temperature, and gravitational acceleration applied to the inorganic material, can be appropriately determined depending on the type and amount of the inorganic material to be treated.

[0039] The rotation speed of the cylindrical container in step (B1) is not particularly limited as it can be appropriately determined depending on the type of inorganic material and the processing amount, but is, for example, 30 rpm or more and 200 rpm or less, preferably 60 rpm or more and 120 rpm or less. In addition, the rotation speed of the cylindrical container is preferably equal to or lower than the critical rotation number. Here, the critical rotation speed is the speed at which the centrifugal force of the grinding balls balances with gravity, causing the grinding balls to rotate in close contact with the inner wall of the cylindrical container. The critical rotation speed (Nc) is expressed as Nc [rpm] = 42.3 / √D when the diameter of the grinding balls can be ignored compared to the inner diameter D [m] of the cylindrical container.

[0040] In the method for producing an inorganic material according to this embodiment, in step (B2), the inorganic material can be moved in the cylindrical axis direction, for example, by reciprocating the cylindrical container in the cylindrical axis direction and / or by reciprocating at least one end of the cylindrical container in a direction perpendicular to the cylindrical axis direction.

[0041] The speed of the reciprocating motion in step (B2) is not particularly limited as it can be appropriately determined depending on the type of inorganic material and the amount of processing, but is, for example, 1 cpm or more and 30 cpm or less, and preferably 2 cpm or more and 6 cpm or less.

[0042] The diameter of the grinding balls is, for example, 0.1 mm or more and 10.0 mm or less, and from the viewpoint of obtaining an even smaller average particle size, it is preferably 1.0 mm or more and 3.0 mm or less.

[0043] In the method for producing an inorganic material according to the present embodiment, the grinding balls preferably include two or more types of grinding balls having different diameters, and more preferably include three or more types of grinding balls having different diameters, which makes it possible to obtain an inorganic material having a smaller average particle size. In the method for producing an inorganic material according to this embodiment, the grinding balls preferably include first grinding balls having a diameter in the range of 1.5 mm to 2.5 mm and second grinding balls having a diameter in the range of 0.2 mm to less than 1.5 mm, and more preferably include third grinding balls having a diameter in the range of more than 2.5 mm to 10.0 mm in addition to the first and second grinding balls. This makes it possible to obtain an inorganic material with an even smaller average particle size.

[0044] At least the surface of the grinding balls is preferably made of at least one material selected from ceramic materials and metal materials. Examples of metal materials include centrifugally chilled steel, SUS, Cr-plated SUS, and Cr-plated hardened steel. Furthermore, when at least the surface of the grinding ball in this embodiment is made of a ceramic material, it is possible to prevent unnecessary metal components derived from the grinding ball from being mixed into the obtained inorganic material, making it possible to obtain an inorganic material with even higher purity. Examples of such ceramic materials include stabilized zirconia, alumina, silicon carbide, and silicon nitride.

[0045] In the method for producing an inorganic material according to this embodiment, a step of classifying the first inorganic material may be performed before step (B) if necessary. By removing coarse particles from the first inorganic material by the classification operation, the first inorganic material can be more effectively microparticulated in step (B). The classification method is not particularly limited, and a known method such as a sieve can be used.

[0046] The second inorganic material obtained by the method for producing an inorganic material according to the present embodiment is not particularly limited, but may have an average particle diameter d 50 However, it is preferably 0.01 μm or more and 20 μm or less, more preferably 0.05 μm or more and 10 μm or less, even more preferably 0.10 μm or more and 8.0 μm or less, even more preferably 0.10 μm or more and 5.0 μm or less, and even more preferably 0.50 μm or more and 4.0 μm or less. Average particle size d of the second inorganic material 50 By setting the value of the surface area within the above range, good handleability can be maintained and, for example, the energy density of an all-solid-state lithium ion battery can be further improved.

[0047] (Annealing process) In the method for producing an inorganic material according to the present embodiment, an annealing step for crystallizing at least a part of the inorganic material may be further carried out in order to further improve the lithium ion conductivity of the resulting inorganic material. The annealing step may be carried out before or after step (B), but is preferably carried out after step (B) in order to obtain a smaller average particle size. By carrying out the annealing treatment, at least a part of the inorganic material in a glass state can be crystallized to become an inorganic material in a glass ceramic state, which can provide an inorganic material with even better lithium ion conductivity, for example.

[0048] The temperature at which the inorganic material in a glassy state is heated is not particularly limited as long as it is a temperature at which crystallization can be sufficiently promoted. For example, from the viewpoint of effectively promoting crystallization while suppressing thermal decomposition of the inorganic material, the temperature is preferably in the range of 220°C or higher and 500°C or lower, preferably in the range of 250°C or higher and 400°C or lower, more preferably in the range of 260°C or higher and 350°C or lower, and even more preferably in the range of 270°C or higher and 350°C or lower. The time for heating the inorganic material is not particularly limited as long as the inorganic material in the desired glass-ceramic state is obtained, but is, for example, within the range of 1 minute to 24 hours, preferably within the range of 0.5 hours to 8 hours, and more preferably within the range of 1 hour to 3 hours. The heating method is not particularly limited, but an example of the method is a method using a firing furnace. The conditions such as the temperature and time during such heating can be appropriately adjusted to optimize the properties of the inorganic material.

[0049] Furthermore, the inorganic material is preferably heated, for example, in an inert gas atmosphere, which can prevent deterioration (for example, oxidation) of the inorganic material. Examples of the inert gas used when heating the inorganic material include argon gas, helium gas, and nitrogen gas. These inert gases are preferably as pure as possible in order to prevent impurities from being mixed into the product, and the dew point is preferably -30°C or less, more preferably -50°C or less, and particularly preferably -60°C or less in order to avoid contact with moisture. The method of introducing the inert gas into the mixed system is not particularly limited as long as the mixed system is filled with an inert gas atmosphere, and examples of the method include a method of purging the inert gas and a method of continuously introducing a constant amount of the inert gas.

[0050] In the annealing process, it is preferable to perform the annealing process until a diffraction peak different from that of the inorganic material in a glass state is observed in a spectrum obtained by X-ray diffraction using CuKα radiation as a radiation source. Here, the observation of a diffraction peak different from that of the inorganic material in a glass state is considered to mean that at least a part of the inorganic material in a glass state has crystallized and become a glass ceramic state. Furthermore, when X-ray diffraction analysis is performed using CuKα radiation as a radiation source, if a new diffraction peak different from the diffraction peak of an inorganic material in a glassy state is generated, it can be determined that the inorganic material has been annealed and has become in a glass-ceramic state.

[0051] (Process (C)) Fig. 2 is a schematic top view of a separation device 30 used in step (C) of the production method for an inorganic material according to embodiment 1. Fig. 3 is a schematic cross-sectional view taken along line AA' of Fig. 2.

[0052] In FIG. 2 and FIG. 3, the first direction X is a direction parallel to the horizontal direction perpendicular to the vertical direction. The second direction Y is a direction parallel to the horizontal direction and perpendicular to the first direction X. The third direction Z is a direction parallel to the vertical direction. The arrows indicating the first direction X, the second direction Y, or the third direction Z indicate that the direction from the base end of the arrow to the tip is the positive direction of the direction indicated by the arrow, and the direction from the tip of the arrow to the base end is the negative direction of the direction indicated by the arrow. The white circle with a black dot indicating the first direction X, the second direction Y, or the third direction Z indicates that the direction from the back of the paper to the front is the positive direction of the direction indicated by the arrow, and the direction from the front of the paper to the back is the negative direction of the direction indicated by the arrow. The positive direction of the third direction Z is the upward direction in the vertical direction, and the negative direction of the third direction Z is the downward direction in the vertical direction. The same applies to the first direction X, the second direction Y, and the third direction Z in the figures described later.

[0053] The separation device 30 includes a container 310 and an agitating unit 320. The container 310 contains at least one grinding ball (not shown in FIGS. 2 and 3) after step (B). The grinding ball after step (B) has a second inorganic material attached thereto. The agitating unit 320 is provided in the container 310. The agitating unit 320 has a shaft 322 and a plurality of blades 324.

[0054] Container 310 has a cylindrical shape with an open upper end and a closed lower end. The side surface of container 310 is made of mesh member 312. Mesh member 312 is made of a metal such as SUS304. Mesh member 312 may be provided on the entire side surface of container 310, or may be provided on only a portion of the side surface of container 310. The volume of container 310 is not particularly limited, but is, for example, 0.5 L or more and 2.0 L or less.

[0055] The shaft portion 322 extends parallel to the third direction Z. The plurality of blades 324 are attached to the sides of the shaft portion 322. When viewed from the third direction Z, the plurality of blades 324, specifically, four plate-shaped blades 324, are arranged at equal intervals along the circumferential direction of the shaft portion 322. The number and arrangement of the blades 324 attached to the shaft portion 322 are not limited to the example according to this embodiment. When the shaft portion 322 rotates, the plurality of blades 324 rotate and the grinding balls are stirred. As in the step (B), at least two types of grinding balls having different diameters may be stirred in the container 310. The rotation speed of the shaft portion 322 can be, for example, 1500 rpm or more and 3000 rpm or less. When the grinding balls are stirred, the grinding balls collide with the mesh member 312. In this way, in this embodiment, the grinding balls are stirred inside an area at least partially surrounded by the mesh member 312.

[0056] According to this embodiment, the grinding balls can be brought into contact with the mesh member 312 with a strong force, as compared to the case where the grinding balls are sieved, for example. Therefore, the inorganic material adhering to the grinding balls can be separated from the grinding balls in a short time, as compared to the case where the grinding balls are sieved.

[0057] FIG. 4 is an enlarged schematic view of a portion of the mesh member 312 according to the first embodiment.

[0058] In the mesh member 312, a plurality of holes 314 are arranged in a lattice shape, for example, by using an expanded metal. When viewed in the depth direction of the holes 314, the holes 314 are polygonal, specifically, rhombic. That is, the holes 314 are shaped with corners. In this case, compared to when the holes 314 are shaped without corners, such as a circle or an ellipse, the grinding balls may collide with the corners of the holes 314, and the inorganic material may be more easily scraped off from the grinding balls. The corners may not be strictly sharp, and may be rounded. The holes 314 may also be polygonal, such as a triangle, a square, a pentagon, a hexagon, or an octagon, that is different from a rhombic shape. Alternatively, the holes 314 may be shaped without corners, such as a circle or an ellipse.

[0059] The vertical width WV of the hole 314 is not particularly limited as long as the grinding balls do not pass through the hole 314, but can be, for example, 1.0 mm or more and 3.0 mm or less. The horizontal width WH of the hole 314 is not particularly limited as long as the grinding balls do not pass through the hole 314, but can be, for example, 1.0 mm or more and 3.0 mm or less. In addition, the thickness T of the mesh member 312 is not particularly limited, but can be, for example, 0.50 mm or more and 1.00 mm or less. The size of the hole 314 may differ depending on the position of the container 310, and for example, the size of the hole 314 at the upper part of the container 310 may be different from the size of the hole 314 at the lower part of the container 310.

[0060] At least the surface of the mesh member 312 can be made of a material having a Vickers hardness higher than that of the material constituting the grinding balls. For example, when the grinding balls are made of ZrO2, the mesh member 312 can be made of stainless steel such as SUS304 coated with diamond-like carbon (DLC). If the Vickers hardness of the surface of the mesh member 312 is lower than that of the grinding balls, the grinding balls collide with the mesh member 312, and part of the surface of the mesh member 312 is ground, which may cause impurities to enter the second inorganic material. On the other hand, if the Vickers hardness of the surface of the mesh member 312 is higher than that of the grinding balls, the incorporation of impurities into the second inorganic material can be suppressed. The surface of the mesh member 312 may be made of a material having a Vickers hardness lower than that of the material constituting the grinding balls.

[0061] (Embodiment 2) Fig. 5 is a top schematic view of the separation apparatus 30 according to embodiment 2. Fig. 6 is a side schematic view of the separation apparatus 30 according to embodiment 2. Fig. 7 is a BB' cross-sectional schematic view of Fig. 5. Fig. 8 is an enlarged schematic view of a portion of the mesh member 312 according to embodiment 2. The separation apparatus 30 according to embodiment 2 is similar to the separation apparatus 30 according to embodiment 1, except for the following points.

[0062] In this embodiment, two wing portions 324 are disposed at equal intervals along the circumferential direction of shaft portion 322 when viewed from third direction Z. The number and arrangement of wing portions 324 are not limited to the example according to this embodiment. Furthermore, wing portion 324 is rod-shaped. In this case, the incorporation of impurities into the second inorganic material due to wear of wing portion 324 can be suppressed compared to the case where wing portion 324 is plate-shaped.

[0063] In the mesh member 312, a plurality of holes 314 are arranged in a herringbone shape, for example, by punching metal. When viewed in the depth direction of the holes 314, the holes 314 are elongated. In this case, compared to a case in which the holes 314 are not elongated, such as a circle, the grinding balls may collide with the longitudinal ends of the holes, and the inorganic material may be more easily scraped off from the grinding balls.

[0064] The longitudinal length LL of the holes 314 is not particularly limited as long as the grinding balls do not pass through the holes 314, but can be, for example, 5.0 mm or more and 15.0 mm or less. The lateral length LS of the holes 314 is not particularly limited as long as the grinding balls do not pass through the holes 314, but can be, for example, 0.50 mm or more and 1.50 mm or less. In addition, the thickness T of the mesh member 312 is not particularly limited, but can be, for example, 0.50 mm or more and 1.50 mm or less.

[0065] The mesh member 312 has at least one protruding shape 316 protruding toward the area surrounded by the mesh member 312. The protruding height of the protruding shape 316 is, for example, 0.50 mm or more and 1.50 mm or less. In this embodiment, a plurality of protruding shapes 316 are provided on the inner surface of the container 310. The number of protruding shapes 316 provided on the container 310 may be only one. In this embodiment, a group of protruding shapes 316 aligned in the third direction Z and another group of protruding shapes 316 aligned in the third direction Z alternately with the group of protruding shapes 316 are alternately aligned along the horizontal direction. The layout of the plurality of protruding shapes 316 is not limited to the example according to this embodiment. When the protruding shape 316 is provided, the movement of the grinding balls stirred in the container 310 can be made more complex than when the protruding shape 316 is not provided, and the second inorganic material can be more easily separated from the grinding balls. The protruding shape 316 does not have to be provided.

[0066] (Modification) 9 is a schematic diagram of a separation apparatus 30 according to a modified example. The separation apparatus 30 according to the modified example is similar to the separation apparatus 30 according to the first or second embodiment, except for the following points.

[0067] The separation device 30 includes a spraying machine 330 that sprays pulverized balls (not shown) toward the mesh member 312. The spraying machine 330 is, for example, a shot blasting machine. In this modification, the pulverized balls can be brought into contact with the mesh member 312 with a stronger force than when the pulverized balls are sieved. Therefore, the inorganic material adhering to the pulverized balls can be separated from the pulverized balls in a shorter time than when the pulverized balls are shaken horizontally above the sieve.

[0068] Although the embodiment and modifications of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted. The present invention is not limited to the above-described embodiment or modification, and modifications, improvements, etc. within the scope of achieving the object of the present invention are included in the present invention. For example, in the first and second embodiments and the modification, step (C) includes a step of colliding the grinding balls with a mesh member. However, step (C) may include a step of sieving the grinding balls instead of the step of colliding the grinding balls with the mesh member. Even in this case, the second inorganic material adhering to the grinding balls can be recovered. EXAMPLES

[0069] EXAMPLES Hereinafter, the present invention will be described with reference to examples and comparative examples, but the present invention is not limited to these.

[0070] [1]Measurement method First, the measurement methods used in the following Examples and Comparative Examples will be described.

[0071] (1) Particle size distribution The particle size distribution of the sulfide-based inorganic solid electrolyte material obtained in the examples and comparative examples was measured by a laser diffraction method using a laser diffraction scattering type particle size distribution measuring device (Malvern Instruments, Mastersizer 3000). From the measurement results, the particle size (d 50, average particle size) were calculated.

[0072] (2) Confirmation of aggregates After pulverizing a sulfide-based inorganic solid electrolyte material in a glassy state using a ball mill for a predetermined period of time, the state inside the ball mill was observed to check for the presence or absence of aggregates.

[0073] (3) Checking scanning electron microscope (SEM) images The sulfide-based inorganic solid electrolyte material separated from the grinding balls was observed by SEM to check for the presence or absence of agglomerates.

[0074] <Example 1> (1) Preparation of the first inorganic material A glassy sulfide-based inorganic solid electrolyte material, which is the first inorganic material, was prepared by the following procedure. The raw materials used were Li2S (manufactured by Furukawa Co., Ltd., purity 99.9%), P2S5 (manufactured by Kanto Chemical Co., Ltd.), and Li3N (manufactured by Furukawa Co., Ltd.). First, a raw material inorganic composition was prepared by mixing Li2S powder, P2S5 powder, and Li3N powder (Li2S:P2S5:Li3N=71.1:23.7:5.3 (mol %)) in a glove box. Next, the raw inorganic composition and 6200 g of ZrO2 balls having a diameter of 25 mm were placed in an alumina cylindrical container (internal volume: 5 L) in the glove box, and the cylindrical container was sealed. Next, an alumina cylindrical container was attached to the ball mill, and mechanochemical treatment was performed at 100 rpm for 500 hours to vitrify the raw inorganic composition. Next, the obtained inorganic material was sieved through a sieve with an opening of 20 μm to obtain a glassy sulfide-based inorganic solid electrolyte material (Li 10 P3S 12 The average particle diameter d of the first inorganic material, the sulfide-based inorganic solid electrolyte material in a glass state, was obtained. 50 is 4.5μm, d 10 is 2.0μm, d 90 was 10 μm.

[0075] (2) Preparation of the second inorganic material Next, 300g of a glass-like sulfide-based inorganic solid electrolyte material, which is the first inorganic material, 6200g of ZrO2 balls with a diameter of 2.0 mm, 1200g of ZrO2 balls with a diameter of 1.0 mm, and 1200g of ZrO2 balls with a diameter of 5.0 mm were put into an alumina cylindrical container (capacity 5L) in a glove box, and the cylindrical container was sealed. Next, the alumina cylindrical container was attached to a ball mill and ground for 50 hours to finely pulverize the first inorganic material, thereby obtaining a second inorganic material. Here, as shown in FIG. 1(a), the cylindrical container 100 was placed on a rotating table 101, rotated at 100 rpm around the cylindrical axis X, and rocked up and down to reciprocate both ends of the cylindrical container 100 in the direction perpendicular to the cylindrical axis X with a rocking frequency of 3 cpm.

[0076] The average particle diameter d of the obtained second inorganic material, the sulfide-based inorganic solid electrolyte material in a glass state, 50 is 2.0μm, d 10 is 1.0μm, d 90 was 3.0 μm. In addition, the glassy sulfide-based inorganic solid electrolyte material (Li 10 P3S 12 After the grinding of the powder was completed, no agglomerates of the glassy sulfide-based inorganic solid electrolyte material were observed inside the ball mill.

[0077] (3) Separation of the second inorganic material As the separation device, a rice polishing machine RSF-A100 manufactured by Tiger Corporation was prepared. The rice polishing machine according to Example 1 has a similar configuration to the separation device 30 according to the first embodiment, and includes a container and an agitation unit.

[0078] The container is cylindrical with an open top and closed bottom, with an internal volume of 1.0 L. As in the example shown in Fig. 4, the side of the container is a 0.8 mm thick SUS304 mesh member made of expanded metal with multiple diamond-shaped holes arranged in a lattice pattern, the length being 2.9 mm and the width being 2.1 mm at the bottom of the container, and the length being 2.8 mm and the width being 2.5 mm at the top of the container.

[0079] Similar to the examples shown in Figs. 2 and 3, the stirring section has a shaft section and four plate-shaped blade sections arranged at equal intervals along the circumferential direction of the shaft section.

[0080] After the above (2) second inorganic material was prepared, 500 g of the 2.0 mm diameter ZrO2 balls, 1.0 mm diameter ZrO2 balls, and 5.0 mm diameter ZrO2 balls were placed in the container of a rice milling machine, and the shaft was rotated at 2000 rpm to stir the ZrO2 balls for 30 seconds. By comparing the total mass of the ZrO2 balls before the above (2) second inorganic material was prepared and the total mass of the ZrO2 balls after the above (2) second inorganic material was prepared, it was estimated that 0.106 g of the second inorganic material was attached to the ZrO2 balls per 1 g of ZrO2 balls. After stirring, 52.7 g of the second inorganic material separated from the ZrO2 balls was recovered. In other words, the recovery rate of the second inorganic material was 99.4%.

[0081] Fig. 10 is a diagram showing SEM images of the second inorganic material separated from the grinding balls in Example 1. The upper image in Fig. 10 is an image at a magnification of 5000 times, and the lower image in Fig. 10 is an image at a magnification of 1000 times. As shown in Fig. 10, almost no aggregates were observed.

[0082] <Example 2> (1) Preparation of a first inorganic material and (2) Preparation of a second inorganic material (1) Preparation of the first inorganic material and (2) preparation of the second inorganic material in Example 2 were similar to the preparation of the (1) preparation of the first inorganic material and (2) preparation of the second inorganic material in Example 1.

[0083] (3) Separation of the second inorganic material As the separation device, a rice polishing machine RCI-B5-W manufactured by IRIS OHYAMA Co., Ltd. was prepared. The rice polishing machine according to Example 2 has a similar configuration to the separation device 30 according to the second embodiment, and includes a container and an agitation unit.

[0084] The container is cylindrical with an open top and closed bottom, and has an internal volume of 1.0 L. As in the example shown in FIG. 8, the side of the container is a 0.8 mm thick SUS304 mesh member with a herringbone pattern of multiple long holes with a longitudinal length of about 9 mm and a lateral length of about 1 mm, formed by punching metal. As in the examples shown in FIGS. 5 to 8, the inner wall of the container is provided with three vertically aligned protrusions and four vertically aligned protrusions that are staggered with respect to the three protrusions, and are alternately arranged along the horizontal direction. The protrusion height of the protrusions is about 1 mm.

[0085] Similar to the examples shown in Figs. 5 to 7, the stirring section has a shaft section and two rod-shaped blade sections arranged at equal intervals along the circumferential direction of the shaft section.

[0086] After the above (2) second inorganic material was prepared, 400 g of the 2.0 mm diameter ZrO2 balls, 1.0 mm diameter ZrO2 balls, and 5.0 mm diameter ZrO2 balls were placed in the container of a rice milling machine, and the shaft was rotated at 2000 rpm to stir the ZrO2 balls for 30 seconds. By comparing the total mass of the ZrO2 balls before the above (2) second inorganic material was prepared and the total mass of the ZrO2 balls after the above (2) second inorganic material was prepared, it was estimated that 0.106 g of the second inorganic material was attached to the ZrO2 balls per 1 g of ZrO2 balls. After stirring, 42.2 g of the second inorganic material separated from the ZrO2 balls was recovered. In other words, the recovery rate of the second inorganic material was 99.5%.

[0087] FIG. 11 is a view showing SEM images of the second inorganic material separated from the grinding balls in Example 2. The upper image in FIG. 11 is an image at a magnification of 5000 times, and the lower image in FIG. 11 is an image at a magnification of 1000 times. As shown in FIG. 11, almost no aggregates were observed. Furthermore, the aggregates observed in Example 2 were smaller than those observed in Example 1.

[0088] <Comparative Example> As shown in FIG. 1(b), a sulfide-based inorganic solid electrolyte material in a glass state was produced in the same manner as in the example, except that the cylindrical container 100 was not shaken up and down (i.e., step (B2) was not performed). The average particle diameter d of the obtained second inorganic material, the sulfide-based inorganic solid electrolyte material in a glass state, 50 is 9.8μm, d 10 is 4.0μm, d 90 was 14.7 μm. In addition, the glassy sulfide-based inorganic solid electrolyte material (Li 10 P3S 12 After the grinding of the powder was completed, aggregates of the sulfide-based inorganic solid electrolyte material in a glassy state were observed inside the ball mill.

[0089] From a comparison between Examples 1 and 2 and the Comparative Example, it can be seen that the manufacturing method of the Example in which step (B2) was performed suppresses the generation of agglomerates and produces an inorganic material with a smaller average particle size. In addition, when step (B2) is performed, it can be said that it is possible to adhere the second inorganic material to the grinding balls rather than to the inner wall of the cylindrical container, compared to when step (B2) is not performed. Furthermore, it can be said that it is possible to recover the second inorganic material adhered to the grinding balls by performing step (C).

[0090] This application claims priority based on Japanese Patent Application No. 2020-173894, filed on October 15, 2020, the disclosure of which is incorporated herein in its entirety. [Explanation of symbols]

[0091] 30 Separation device 100 Cylindrical container 101 Rotating platform 310 Container 312 Mesh material 314 holes 316 Protrusion shape 320 Stirring section 322 Shaft 324 Wing X Cylinder Axis

Claims

[Claim 1] A step (A) of preparing a first inorganic material as a raw material; (B) a step of pulverizing the first inorganic material using a ball mill having a cylindrical container and pulverizing balls to obtain a second inorganic material by microparticulating the first inorganic material; (C) a step of separating the second inorganic material from the grinding balls to which the second inorganic material is attached; Including, The step (B) includes a step (B1) of rotating the cylindrical container about a cylindrical axis after placing the first inorganic material and the grinding balls in the cylindrical container, and a step (B2) of moving the cylindrical container so that the first inorganic material moves in the cylindrical axis direction. A method for producing an inorganic material comprising the steps of:

Citation Information

Patent Citations

  • Ball milling equipment for lithium battery material processing

    CN108940471A

  • Oblique shaft ball mill

    JP1985031836A

  • Dry pulverizing method and ball mill

    JP2005066406A

  • Pulverizer

    JP2007190480A

  • Centrifugal ball mill

    JP2014111246A